Bone Volume Fraction and Fabric Anisotropy Are Better Determinants of Trabecular Bone Stiffness Than Other Morphological Variables. (June 2015) - Maquer, Ghislain; Musy, Sarah N; Wandel, Jasmin; Gross, Thomas; Zysset, Philippe K
ABSTRACT As our population ages, more individuals suffer from osteoporosis. This disease leads to impaired trabecular architecture and increased fracture risk. It is essential to understand how morphological and mechanical properties of the cancellous bone are related. Morphology‐elasticity relationships based on bone volume fraction (BV/TV) and fabric anisotropy explain up to 98% of the variation in elastic properties. Yet, other morphological variables such as individual trabeculae segmentation (ITS) and trabecular bone score (TBS) could improve the stiffness predictions. A total of 743 micro–computed tomography (μCT) reconstructions of cubic trabecular bone samples extracted from femur, radius, vertebrae, and iliac crest were analyzed. Their morphology was assessed via 25 variables and their stiffness tensor (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn7q9gn4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CFE</alternatives>) was computed from six independent load cases using micro finite element (μFE) analyses. Variance inflation factors were calculated to evaluate collinearity between morphological variables and decide upon their inclusion in morphology‐elasticity relationships. The statistically admissible morphological variables were included in a multiple linear regression model of the dependent variable <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn7q9gq5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CFE</alternatives>. The contribution of each independent variable was evaluated (ANOVA). Our results show that BV/TV is the best determinant of <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjn7q9grp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CFE</alternatives>(r2adj = 0.889), especially in combination with fabric anisotropy (r2adj = 0.968). Including the other independent predictors hardly affected the amount of variance explained by the model (r2adj = 0.975). Across all anatomical sites, BV/TV explained 87% of the variance of the bone elastic properties. Fabric anisotropy further described 10% of the bone stiffness, but the improvement in variance explanation by adding other independent factors was marginal (<1%). These findings confirm that BV/TV and fabric anisotropy are the best determinants of trabecular bone stiffness and show, against common belief, that other morphological variables do not bring any further contribution. These overall conclusions remain to be confirmed for specific bone diseases and postelastic properties. © 2015 American Society for Bone and Mineral Research.